2021
DOI: 10.3390/ijms22030998
|View full text |Cite
|
Sign up to set email alerts
|

Reticular Basement Membrane Thickness Is Associated with Growth- and Fibrosis-Promoting Airway Transcriptome Profile-Study in Asthma Patients

Abstract: Airway remodeling in asthma is characterized by reticular basement membrane (RBM) thickening, likely related to epithelial structural and functional changes. Gene expression profiling of the airway epithelium might identify genes involved in bronchial structural alterations. We analyzed bronchial wall geometry (computed tomography (CT)), RBM thickness (histology), and the bronchial epithelium transcriptome profile (gene expression array) in moderate to severe persistent (n = 21) vs. no persistent (n = 19) airf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…Asthma patients with persistent airflow limitation were characterized by altered airway geometry, mainly increased WTR and WAR in the right bronchi, compared to patients without persistent airflow limitation, which stays in line with previously published reports [12,13,27]. In contrast, well-defined signs of remodeling in bronchial mucosae, such as RBM thickness and collagen deposits [11], were comparable in both studied subgroups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Asthma patients with persistent airflow limitation were characterized by altered airway geometry, mainly increased WTR and WAR in the right bronchi, compared to patients without persistent airflow limitation, which stays in line with previously published reports [12,13,27]. In contrast, well-defined signs of remodeling in bronchial mucosae, such as RBM thickness and collagen deposits [11], were comparable in both studied subgroups.…”
Section: Discussionsupporting
confidence: 90%
“…Various features of airway remodeling, such as loss of epithelial cells and mucus cell hyperplasia, RBM thickening, and smooth muscle hypertrophy, can be described using a histological examination of airway mucosa [11]. However, emerging non-invasive methods, including lung computed tomography (CT) imaging, provide important remodeling measures that might be useful in quantifying bronchial wall thickening in a standardized and more comprehensive way [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…RNF13 plays a role in myogenesis, tumorigenesis, and cell proliferation [29,32,33]. Recent studies have shown that RNF13 expression in atherosclerosis plaques is upregulated [34], while it is downregulated in uveal melanoma [35] and asthma [36]. Ectopic expression of RNF13 inhibits myoblast proliferation, whereas treatment with myostatin, a muscle growth inhibitor, upregulates RNF13 expression [32].…”
Section: Introductionmentioning
confidence: 99%
“…RNF13 altered expression is not only linked to cancer. In fact, recent studies have shown that RNF13 gene expression is upregulated in atherosclerotic plaques [70] and downregulated in asthma [71]. Also, Huang et al discovered that the microRNA miR-32-3p regulates the expression of RNF13 [72].…”
Section: Atherosclerotic Plaquesmentioning
confidence: 99%